The Effect of Thermal Ageing on the Mechanical Properties of Natural Rubber-based Compounds Used for Rubber Bearings - Manuel Alberto Guzmán; Diego Hernán Giraldo-Vásquez; Ricardo Moreno (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Molecular changes due to high temperatures, sunlight, and oxygen, deteriorate the physical properties of rubber compounds, yielding additional crosslinks and molecular chain breakdown. Since oxidative degradation is the most important factor that determines the durability of rubber components, this study evaluated the mechanical behavior of rubber compounds exposed to accelerated thermal ageing. Therefore, three carbon black-reinforced natural rubber-based compounds typically used for rubber bearings were exposed to thermal oxidation and their mechanical properties under typical loading states were assessed through standardized tests. Significant differences were found due to thermal ageing in the compressive modulus, compression set, and creep compliance in compression, exhibiting a stiffening effect caused by additional crosslinks. However, no significant differences were observed in hardness, which is a superficial measurement and a typical test in the rubber industry to characterize rubber compounds. Therefore, the assessment of ageing in rubber bearings should not be limited to a hardness test, which is required in design standards but also addresses compressive, cyclic, and transient tests. The results obtained in this study can be considered in the design process of rubber bearings by limiting the allowable compressive stress and creep deflection due to ageing effects.